Analisis Penerapan Artificial Intelligence terhadap Efektifitas Kinerja Pegawai - Sri Iswati; Niken Saraswati; Sari Mulyana (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
Technological developments in the industrial era 4.0 and 5.0 have brought humans to increasingly rapid needs, so humans are making artificial intelligence (AI) into various sectors, including in human resource management (HR) to streamline performance. This research aims to analyze the application of artificial intelligence to the effectiveness of employee performance at the Education and Training Agency of the Ministry of Defense (Badiklat Kemhan). The research method used is the Mix Method with a Concurrent Embedded Strategy approach, which combines quantitative and qualitative data. The population was 389 and processed using a simple size calculator there were 161 respondents. The research results show that more than 70% of employees at the Ministry of Defense's Education and Training Center have felt an increase in performance effectiveness after implementing A.I. AI technology has helped speed up task completion, improve work quality, and support more informed decision making. The interview results show that the application of AI can support work in increasing insight and enriching teaching materials, thus helping in creating slides, articles and videos that are relevant to the teaching topic, as well as providing recommendations for teaching resources to decision makers. The majority of respondents showed a desire to be able to learn and improve skills in using AI, showing awareness of the importance of self-development in the era of digitalization. This research refers to the importance of ongoing training to maximize the potential use of A.I.highlighting the importance of self-development in the digital era. This study emphasizes the importance of continuous training to maximize the potential of AI usage.